Circuitos económicos solidarios, en las organizaciones de producción de panela orgánica de la parroquia de Pacto - Arcos Torres, Manuela Sinaí (2017)
In the parish of Pacto in the northwest of Pichincha, producers of organic panela have joined to promote the improvement of sugarcane planting, implement and homogenize the production of organic suger cane and achieve the direct marketing of the product. The work of systematization presented in this document, includes three of the organizational experiences of producers of suger cane, COPROPAP, Summits of Ingapi, and COLSPA, sought to understand the form of organization, the objectives, as well as solidarity circuits within and between the organizations, the relationship you are with other institutions present in the parish. It tries to identify elements of solidarity networks and circuits that give way to elements of social and solidarity economy. The approach to productive experiences, allow us to observe the discussion that is generated within the organizations, from the search to implement organic production forms.